Parallels between structural estimation and causal inference: A discussion of Armstrong et al. (2022) - Whited, Toni M. (Journal of Accounting and Economics, 2022)
Armstrong et al. (2022) review the various econometric methods that have been used to draw causal inference in the accounting literature and offer an alternative method for conducting research when causal methods are not applicable. This discussion provides background for the emphasis on causal inference in accounting. It also draws parallels between the authors' proposed quasi-causal method and the structural estimation methods that have been used in finance and that are starting to be used in accounting.